Time Trends and Policy Gaps: The Case of Alcohol Misuse Among Adolescents in Lebanon. (6th December 2015) - Ghandour, Lilian; Afifi, Rima; Fares, Sonia; El Salibi, Noura; Rady, Alissar
Abstract : Background : Monitoring studies are crucial for informing and reforming local policies. Objectives : Using the Lebanon 2005 and 2011 Global School-based Student Health Surveys (GSHS), alcohol time trends were described, policy gaps were identified, and harm reduction policy recommendations were made. Methods : In 2005 and 2011, 100 ( n = 5109 students) and 44 ( n = 2784 students) middle schools were surveyed, respectively. Self-reported cross-sectional data on alcohol use among 7–9th graders in private and public schools was collected including 30-day prevalence, lifetime drunkenness, alcohol-related problems, and sources of alcohol. Results : In 2011, the majority (87%) had alcohol before turning 14. Between 2005 and 2011, past 30-day alcohol use had increased by 40% and lifetime drunkenness by 50% in the total sample (122% among females with a narrowing in the gender gap). Drinking was regular for more than a third of the past 30-day drinkers (drank two or more drinks on the days they drank). Male adolescents were more likely to obtain alcohol from "stores" or "through their friends" whereas females' main source was their "family." One in twenty reported experiencing alcohol-related problems (e.g., getting into fights with family/friends and skipping school). Conclusion/Importance : Evidence-informed policy implications include enforcing a minimum legal drinking age, regulating alcohol advertising, and marketing particularly those targeting youth and women, and ensuring the availability of youth-friendly services. Public messages to increase awareness among all stakeholders including youth, their parents, and larger community are also needed.